Memoir 202: The Greenland Caledonides: Evolution of the Northeast Margin of Laurentia 2008
DOI: 10.1130/2008.1202(13)
|View full text |Cite
|
Sign up to set email alerts
|

Laurentian margin evolution and the Caledonian orogeny—A template for Scotland and East Greenland

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 184 publications
0
24
0
Order By: Relevance
“…However, available data suggest that rifting progressed from northeast to southwest in present coordinates, being the oldest in Baltica (Bingen et al 1998) and becoming younger in Scotland (e.g. Leslie et al 2008) and the Appalachians (van Staal et al 1998;Burton and Southworth 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, available data suggest that rifting progressed from northeast to southwest in present coordinates, being the oldest in Baltica (Bingen et al 1998) and becoming younger in Scotland (e.g. Leslie et al 2008) and the Appalachians (van Staal et al 1998;Burton and Southworth 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Karabinos et al1998;Hibbard et al 2007;van Staal et al 2007;van Staal and Hatcher 2010;Leslie et al 2008;Chew et al 2008Chew et al , 2010Allen et al 2010). Laurentia's Appalachian -Caledonian margin may therefore have been characterised by large, magmapoor, hyperextended segments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are, from youngest to oldest, as follows. 1) Leslie et al (2008) and Prave et al (2009b) correlated the Loch na Cille Boulder Bed (Elles 1934;Prave 1999), which marks the top of the Tayvallich Volcanic Formation in SW Scotland (Pickett, in press), with the Inishowen glacial beds in Donegal (Condon & Prave 2000) and the Macduff Boulder Bed in NE Scotland (Stoker et al 1999). They suggested that these units represent the Gaskier global glacial event (c. 580 Ma).…”
Section: Age Of Volcanismmentioning
confidence: 99%
“…The Crinan Subgroup is characterised by thick sedimentary units and deep water turbiditic facies, which may represent the onset of a rift-to-drift transition (Leslie et al 2008). During this period volcanic activity was relatively low.…”
Section: Crinan and Tayvallich Subgroupsmentioning
confidence: 99%